2022
DOI: 10.1155/2022/6459029
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-331-3p Affects the Proliferation, Metastasis, and Invasion of Osteosarcoma through SOCS1/JAK2/STAT3

Abstract: MicroRNAs (miRNAs) are regulatory small noncoding RNAs that play a key role in several types of cancer. It has been reported that miR-331-3p is involved in the development and progression of various cancers, but there are few reports regarding osteosarcoma (OS). The public GEO database was used to analyze the survival difference of miR-331-3p in OS organizations. The level of cell proliferation assay was assessed by CCK-8 and colony formation. First, transwell and wound-healing assays were used to detect the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Loss of SOCS1 may increase immune evasion and in ammation, potentially playing a role in the development of osteosarcoma [30,31]. Further research shows that enhancing the expression of SOCS1 can impede osteosarcoma cell proliferation, invasion, induce cell apoptosis, and inhibit tumour angiogenesis [32]. Additionally, previous research has highlighted the targeting relationship between miR-155 and SOCS1.…”
Section: Discussionmentioning
confidence: 97%
“…Loss of SOCS1 may increase immune evasion and in ammation, potentially playing a role in the development of osteosarcoma [30,31]. Further research shows that enhancing the expression of SOCS1 can impede osteosarcoma cell proliferation, invasion, induce cell apoptosis, and inhibit tumour angiogenesis [32]. Additionally, previous research has highlighted the targeting relationship between miR-155 and SOCS1.…”
Section: Discussionmentioning
confidence: 97%
“…Differential expression analysis showed 12 downregulated genes (mostly associated with the negative regulation of transcription: NFKBIB , BTRC , CREBBP , HDAC1 , NCOR2 , and FBXW11 ) and 19 upregulated genes [mostly associated with protein ubiquitination ( SOCS1 , RBX1 , RPS27A , UBB , UBA52 , and UBE2N ), positive regulation of cell proliferation ( CTNNB1 , NRAS , HRAS , CDKN1A , and STAT3 ), and cell surface receptor signaling pathways ( IL6 , IFNA5 , IFNA7 , IFNA16 , and NGF ) in OS samples compared to controls. Several of these genes have already been associated with OS pathophysiology [ 149 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ]. Moreover, KEGG functional enrichment was assessed through STRING v12 (available at accessed on 17 April 2024) and showed that under-expressed genes belonged mainly to MAPK and WNT signaling pathways, while upregulated genes belonged to the PI3K/AKT and JAK/STAT cascades ( Figure 6 C), reinforcing the concept of NF-κB as a common player underneath OS establishment and progression.…”
Section: Nf-κb Dysregulation and Cancermentioning
confidence: 99%
“…Numerous studies have explored the strong association between miRNAs and the development of osteosarcoma. For instance, miR-18b-5p, miR-331-3p, and miR-744-5p have shown tumor-suppressive functions involving the growth, proliferation, metastasis, and invasion of osteosarcoma cells [11][12][13]. Previous research has indicated that the EGF-mediated reduction of miR-92a-1-5p regulates HTR-8/SVneo cell invasion through the activation of MAPK8 and FAS, leading to a subsequent increase in MMP-2 and MMP-9 expression [14].…”
Section: Introductionmentioning
confidence: 99%